Determinants of TB Treatment Failure in Pasuruan: A Mixed-Methods Spatial Study - Ida Zuhroidah; Isna Qadrijati; Harsini (NurseLine Journal, 2026)
Introduction: Pulmonary tuberculosis (TB) remains one of the leading causes of death from infectious diseases and poses a serious threat to global health. Indonesia ranks second after India in the TB burden. In Pasuruan City, TB cases continue to increase, indicating a persistent public health problem. Objective: This study aimed to analyze the distribution of pulmonary TB cases and identify factors associated with treatment failure. Method: This study employed a mixed-methods design with a descriptive-analytical approach conducted in Pasuruan City from 2020 to 2024. Distribution of pulmonary TB cases were obtained from secondary data from reports of Pasuruan City Health Office, including TB case reports and treatment outcomes. Primary data were collected from 42 patients with treatment failure using structured questionnaires to assess demographic, clinical, and behavioral factors. In-depth interviews were conducted with 15 purposively selected participants to explore contextual factors influencing treatment adherence. Environmental observations were also performed in high-incidence areas to assess housing density, ventilation, and sanitation conditions. Quantitative data were analyzed using descriptive statistics, Chi-square tests, and binary logistic regression, while qualitative data were analyzed using thematic analysis. Results: TB cases increased from 590 in 2020 to 898 in 2023, with a slight decrease in 2024 (893 cases), while drug-resistant TB remained relatively stable. Cases were concentrated in high-burden areas, including Trajeng, Gadingrejo, and Kebonagung. Non-adherence to medication (OR: 3.2), comorbid diabetes mellitus (OR: 2.1), and limited access to health services (OR: 2.5) were identified as significant risk factors for treatment failure. Family support, economic conditions, and transportation influence patient behavior in adherence to TB treatment. Conclusion: Pulmonary TB in Pasuruan City is increasing and spatially clustered in high-risk areas. Behavioral, clinical, and access-related factors influence treatment failure.